Redesigning Teacher's Roles Towards A Learners' Autonomous Education. - Ahmad, Norlida; Yaakub, Rohizani (2003)

(untitled)
Rapid changes in information communication technology have urged the Malaysian Education Ministry to review the nation's curriculum to place more focus on English. In the year 2003 the ministry decides subjects such as mathematics and science in schools be taught in English in order to enhance students' ability and capability to cope with the advancement of learning strategies in the new millennium.